The genus Prosopis (Leguminosae) in the Province of La Pampa (Argentine) (Semiárida, 2020)
The present study of the genus Prosopis L. emend. BUrXart(Leguminosas Juss.), In the Province of La Pampa, Argentine, Is based on the extemal morphology. As a result 7 species, 6 varletles and 1 form are recognized, of which 2 species, 2 varieties and 1 form are cited for tlrst time for this province. A key for the Identification of the entitles, synonymy, common names, Ranquel Indian names, a description, the general distribution and their diffusion In La Pampa and a discussion of the characteristics and qualities; are given. A Iist of the studied herbarium specimens la included.